Influence of Ti and Zn on particle incorporation of AlB2, B and B4C particles in aluminum using the stir casting process - Plötz, Steven; Lohmüller, Andreas; Singer, Robert (Key Engineering Materials, 2017)
The outstanding performance of many aluminum matrix composites (AMCs) regarding specific stiffness makes AMCs attractive materials for lightweight construction. Low density boride compounds promise both an increase in stiffness and decrease in composite density. Therefore for this study AlB2, B and B4C were chosen for composite manufacturing. The composites were fabricated with the stir casting process. To avoid gas entrapment during mixing and ensure nonporous composites, partial vacuum was adapted during particle feeding and stirring. Poor wettability of used particle material in contact with liquid aluminum hindered particle incorporation, but alloying elements such as titanium were shown to affect wettability and particle incorporation for B4C. Zn had no influence on wettability or reactivity and did not improve particle incorporation. In contrast to Zn, Ti improved adhesion and wettability, but particle incorporation was improved exclusively for B4C. Besides alloying Ti, the use of high-shear force mixers improved particle incorporation enabling uniform particle distribution. AMCs with up to 12 vol.% of B4C particles were produced via stir casting without alloying Ti.
Keywords: Aluminum matrix composites; Boron carbide; Stir casting; Titanium; Wettability

Wettability of Low Weight Borides by Commercial Aluminum Alloys − A Basis for Metal Matrix Composite Fabrication - Plötz, Steven; Nowak, Rafal; Lohmüller, Andreas; Sobzcak, Natalia; Singer, Robert (Advanced Engineering Materials, 2016)
Boron compounds are promising candidates for reinforcement of metals because of their high strength and stiffness at low specific weight. For composite fabrication the wetting behavior is important. Isothermal wetting of BC, AlB, CaB, MgB, and TiB by liquid pure aluminum (99.5%) and the alloy AlSi10MgMn is studied at 700 °C for 15 min in vacuum using the dispensed drop method. No wetting occurs during testing for all substrates. The contact angles remain constant for CaB, MgB, and TiB, while for AlB and BC substrates a continuous decrease in contact angle value with time is observed.